Large and accessible conductivity of charged domain walls in lithium niobate - Werner, Christoph S. (Sci Rep, 2017)
Ferroelectric domain walls are interfaces between areas of a material that exhibits different directions of spontaneous polarization. The properties of domain walls can be very different from those of the undisturbed material. Metallic-like conductivity of charged domain walls (CDWs) in nominally insulating ferroelectrics was predicted in 1973 and detected recently. This important effect is still in its infancy: The electric currents are still smaller than expected, the access to the conductivity at CDWs is hampered by contact barriers, and stability is low because of sophisticated domain structures or proximity of the Curie point. Here, we report on large, accessible, and stable conductivity at CDWs in lithium niobate (LN) crystals – a vital material for photonics. Our results mark a breakthrough: Increase of conductivity at CDWs by more than 13 orders of magnitude compared to that of the bulk, access to the effect via ohmic and diode-like contacts, and high stability for temperatures T ≤ 70 °C are demonstrated. A promising and now realistic prospect is to combine CDW functionalities with linear and nonlinear optical phenomena. Our findings allow new generations of adaptive-optical elements, of electrically controlled integrated-optical chips for quantum photonics, and of advanced LN-semiconductor hybrid optoelectronic devices.